FAKTOR FAKTOR YANG MEMBERIKAN IMPLIKASI TERHADAP KETERIKATAN PEKERJA - Ramaditya, Muhammad; Nazzario, Gabriel (Economic Faculty, Attahiriyah Islamic University, 2020)
Purpose- This study aims to determine the effect of organizational culture, communication, and religiosity on work engagement mediated by work motivation at the Bureau of Personnel and Organization, Main Secretariat of the Financial and Development Supervisory Agency. Design/methodology/approach- The population in this study was 143 Civil Servants (PNS). Samples were taken by a population of 143 people. Data collection techniques using questionnaires and interviews, while the analytical tool used is the Structural Equation Modeling (SEM) using AMOS version 22. Findings- The results of this study indicate that organizational culture, communication, and religiosity do not have a significant positive effect on work motivation and work engagement. Work motivation is not proven as a mediator of cultural, communication, and religiosity relations to work attachment. Implications- To improve the organizational culture of personnel and organization bureaus can be done through enhancing activities that support the re-culture of the organization in the routine activities of the Personnel and Organizations Bureau. Keywords: Culture, Religiosity, Employee Engagement, and Communication